How To Accelerate Digital Transformation in Companies With Lean Philosophy? Contributions Based on a Practical Case - Basulo Ribeiro, Juliana; Amorim, Marlene; Teixeira, Leonor (International Journal of Industrial Engineering and Management, 2023)
The market is constantly changing, requiring adaptation by companies to remain competitive. Many companies have already tried to achieve this goal by using the Lean Philosophy, and now aim to adopt Industry 4.0 practices, such as digitalization. However, there are several studies that report difficulties in adopting these practices, requiring for their success a dedicated and well-defined strategy. The present project arises in this context and aims to propose mechanisms to initiate/accelerate the digital transformation of companies in Lean industrial environments. As results, besides the framework to support the journey in this domain – a roadmap based on Lean and BPM – a technological tool to help companies throughout the digital transformation was also developed and proposed. Thus, theoretically this study contributes to increase knowledge in an emerging area, while guiding business managers in adopting the new digital paradigm from a practical perspective. Article history: Received (December 9, 2022); Revised (March 12, 2023); Accepted (March 21, 2023); Published online (March 24, 2023)